Municipal fragmentation and economic performance in OECD TL2 regions - David Bartolini (European Regional Science Association (ERSA), 2015)
The present work looks at the relationship between institutional structure and economic performance at the regional level. The work focuses on one particular aspect, the number of municipalities in a given region (municipal fragmentation) and the impact on regional development measured as GDP per capita growth. The impact of municipal fragmentation on regional development is not clear a priori. The theory of fiscal decentralisation maintains that institutions closer to citizens can better deal with their needs, thus providing services and public goods in a more efficient way. This closeness, however, implies the presence of many local governments (e.g., municipalities), which may create problems in terms of policy spillovers and (dis)economies of scale. The present work tests the impact of municipal fragmentation on a sample of OECD TL2 regions, in the period 1996-2011. The analysis shows that the impact of fragmentation on regional performance depends on regional territorial characteristics. In particular, the negative impact of fragmentation increases with the share of regional population living in urban areas. In fact, for ?rural? regions the effect is small or even positive where a high share of the population lives in rural areas. This is because the costs and benefits of decentralisation have a different impact in urban and rural regions. In urban regions, the benefit of internalising policy spillovers (and reducing transaction costs) is higher than the loss of proximity, because population is geographically concentrated and commutes more than population in rural areas, where policy spillovers are smaller and the costs associated with the loss of proximity higher. The implications for countries? economic policies are threefold. Firstly, countries should not consider the degree of administrative fragmentation per se, it is important to weight it for the rural index at the regional level. For instance, when considering France as a whole the level of municipal fragmentation is the second highest among OECD countries, but most of this fragmentation stems from rural regions. Secondly, the analysis implicitly recognises the importance of dealing with governance gaps in urban regions; for instance, the lack of co-operation in transport policies is especially detrimental for the performance of metropolitan areas. Thirdly, the overall effect of a reduction of municipal fragmentation would depend on the types of regions within each country. To sum-up, the present work shows the importance of territorial characteristics for administrative performance, thus advocating for a place-based approach to institutional reforms.
Keywords: R11; R50; 330; Regional growth; institution; local government